Africa's Population: In Search of a Demographic Dividend - Groth, Hans; May, John F. (Springer International Publishing : Imprint: Springer, 2017)
This book examines the promises as well as the challenges the demographic dividend brings to sub-Saharan Africa as fertility rates in the region fall and the labor force grows. It offers a detailed analysis of what conditions must be met in order for the region to take full economic advantage of ongoing population dynamics. As the book makes clear, the region will need to accelerate reforms to cope with its demographic transition, in particular the decline of fertility. The continent will need to foster human capital formation through renewed efforts in the areas of education, health and employment. This will entail a true vision and determination on the part of African leaders and their development partners. The book will help readers to gain solid knowledge of the demographic trends and provide insights into socioeconomic policies that eventually might lead sub-Saharan Africa into a successful future. « Africa needs a serious dialogue on population, the demographic transition, and the demographic dividend. This book with its comprehensive approach to the subject, makes an invaluable contribution. A must read for policymakers and development practitioners. » Ngozi Okonjo-Iweala, former Finance Minister of Nigeria and former Managing Director of The World Bank. « Everyone concerned about human welfare in sub-Saharan Africa should know about the demographic dividend, what it is, what causes it and how to strengthen it. This volume provides an excellent summary of these crucial issues. The sooner policymakers pay attention and take the proper actions, the better. » John Bongaarts, Vice President of the Population Council « There is no more important socio-economic issue for this century than that of whether Africa's currently rapid population growth turns out to be a dividend or a curse. As a comprehensive, up-to-date guide to the potential and the challenges, this book deserves to be widely read and debated. » Bill Emmott, former Editor-in-Chief of The Economist « This book is of utmost strategic relevance for any globally active company. For Africa in particular, the role of demographic change and the potential economic opportunities are all too often disregarded. » Reto Francioni, Chairman SWISS International Airlines, former CEO Deutsche Börse.